Adaptive web based tutoring system for medical student : gynecology - Siti Sabilah, Mohd Abdullah (2013)
In higher level of education, student is more independent in their study without having fully lecturer attention such as in high school. This paper discuss on Adaptive Web Based Tutoring System which is created for medical student to provide them with an online education for their better understanding about the theory, process, and concepts through interactive and effective way. This system is design based on three level of adaptation which are basic, intermediate, and advanced for help student in understanding the concept based on their capabilities.